Experience with an IP multimedia system trial for PSTN migration. - Hong-Bin Chiou (IEEE Communications magazine)
In this article, we share our experience of a trial that attempted to gain practical experience in migrating telephony services from the public service telephone network (PSTN) to the IP multimedia system (IMS) domain. We point out some key challenges on the migration path to IMS and identify many issues for successful service deployment in an IMS-based next generation network. Some regulatory concerns and non-technical issues also are addressed.